Inference Strategies To Improve Reading Comprehension of Recount Text - Yayah Nurhidayah; Afief Fakhrudin (Universitas Pancasakti Tegal, 2018)
This study aimed to explore inference strategies necessary read journal article. Forty four English students read set of text on education text and answer comprehension question. The two main objectives in this study were to identify inference skills necessary to comprehend a research article in terms of the main ideas, the writing styl e/tone and other text-based elements such as lexical items, syntaxes well as discourse structures and to investigate inference strategies for coping with text. Twenty five of these participants also volunteered for an in depth interview. The findings revealed that students usually relied on their bottom up processing. They skipped difficult parts, especially technical information graphic illustration. They sought help from friends to enhance their understanding. Overall, they were successful at interpreting the thesis statement, the gist of section, the meaning of the tested words and clause. However, they were less able to infer the underlying argument, the tone of article, and the attitudes of other toward the research finding